Brain Processing of Contagious Itch in Patients with Atopic Dermatitis - Schut, Christina; Mochizuki, Hideki; Grossman, Shoshana K.; Lin, Andrew C.; Conklin, Christopher J.; Mohamed, Feroze B.; Gieler, Uwe; Kupfer, Joerg; Yosipovitch, Gil (Frontiers in Psychology, 2017)
Several studies show that itch and scratching cannot only be induced by pruritogens like histamine or cowhage, but also by the presentation of certain (audio-) visual stimuli like pictures on crawling insects or videos showing other people scratching. This phenomenon is coined “Contagious itch” (CI). Due to the fact that CI is more profound in patients with the chronic itchy skin disease atopic dermatitis (AD), we believe that it is highly relevant to study brain processing of CI in this group. Knowledge on brain areas involved in CI in AD-patients can provide us with useful hints regarding non-invasive treatments that AD-patients could profit from when they are confronted with itch-inducing situations in daily life. Therefore, this study investigated the brain processing of CI in AD-patients. 11 AD-patients underwent fMRI scans during the presentation of an itch inducing experimental video (EV) and a non-itch inducing control video (CV). Perfusion based brain activity was measured using arterial spin labeling functional MRI. As expected, the EV compared to the CV led to an increase in itch and scratching (p < 0.05). CI led to a significant increase in brain activity in the supplementary motor area (SMA), left ventral striatum and right orbitofrontal cortex (OFC) (threshold: p < 0.001; cluster size k > 50). Moreover, itch induced by watching the EV was by trend correlated with activity in memory-related regions including the temporal cortex and the (pre-) cuneus as well as the posterior operculum, a brain region involved in itch processing (threshold: p < 0.005; cluster size k > 50). These findings suggest that the fronto-striatal circuit, which is associated with the desire to scratch, might be a target region for non-invasive treatments in AD patients.